2019
DOI: 10.21873/anticanres.13198
|View full text |Cite
|
Sign up to set email alerts
|

County Median Family Income Is an Independent Prognostic Factor for Stage IV Anaplastic Thyroid Cancer

Abstract: Background/Aim: Advanced anaplastic thyroid cancer (ATC) is a rare, but highly aggressive malignancy, and its prognostic factors need to be further explored. We examined socioeconomic factors' predictive effect for survival performance in stage IV ATC patients. Materials and Methods: Using the Surveillance, Epidemiology, and End Results database, we collected 1,048 cases with stage IV anaplastic thyroid cancer (ATC) from 2004 to 2015. Demographic, clinical, and socioeconomic factors were evaluated using univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“… 18 , 22 , 23 The overall, as well as specific cancer survival, were confirmed to be favourable in married patients. 17 Even though our study did not show any significant association with marital status, it was observed that patients who are married present with early stages frequently than the others. Multiple hypotheses have been proposed in other studies explaining the positive association of being married with a better survival rate.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“… 18 , 22 , 23 The overall, as well as specific cancer survival, were confirmed to be favourable in married patients. 17 Even though our study did not show any significant association with marital status, it was observed that patients who are married present with early stages frequently than the others. Multiple hypotheses have been proposed in other studies explaining the positive association of being married with a better survival rate.…”
Section: Discussioncontrasting
confidence: 81%
“… 15 , 16 It has also been associated with worse prognosis and outcome even after adjusting for the cancer stage. 17 , 18 , 19 However, it is worth mentioning that all those studies were conducted in non-funded hospital systems. In our study, no association between monthly income and thyroid cancer stage is found.…”
Section: Discussionmentioning
confidence: 99%
“…We further quantitatively evaluated the impact of different marital status on cardiovascular death in breast cancer patients. Categorical variables included marital status (married and unmarried), age at diagnosis (25-60 and >60 years) (13), race (white, black and other), income (low and high) (14), grade (low and high), ER status (positive and negative), PR status (positive and negative), HER2 status (positive and negative), AJCC stage (I, II, III and IV), surgery (yes and no evidence), chemotherapy (yes and no evidence) and radiotherapy (yes and no evidence). As for the income, low household income represented the worst 50% among all breast cancer patients, and high household income represented the best 50% among all breast cancer patients (14).…”
Section: Study Population and Designmentioning
confidence: 99%
“…Categorical variables included marital status (married and unmarried), age at diagnosis (25-60 and >60 years) (13), race (white, black and other), income (low and high) (14), grade (low and high), ER status (positive and negative), PR status (positive and negative), HER2 status (positive and negative), AJCC stage (I, II, III and IV), surgery (yes and no evidence), chemotherapy (yes and no evidence) and radiotherapy (yes and no evidence). As for the income, low household income represented the worst 50% among all breast cancer patients, and high household income represented the best 50% among all breast cancer patients (14). Low grade included well differentiated (Grade I) and moderately differentiated (Grade II), while high grade included poorly differentiated (Grade III) and undifferentiated (Grade IV).…”
Section: Study Population and Designmentioning
confidence: 99%
“…Previous studies demonstrated that multiple socioeconomic factors might influence the treatment selection and further prognosis of thyroid cancer, such as insurance status, marital status, living area, etc. [4][5][6][7][8][9][10][11][12]. However, all the above studies focused on either a sole socioeconomic factor or a sole histology subtype.…”
Section: Introductionmentioning
confidence: 99%